Physiological Aldosterone Concentrations Are Associated with Alterations of Lipid Metabolism: Observations from the General Population - M. Hannich; H. Wallaschofski; M. Nauck; M. Reincke; C. Adolf; H. Völzke; R. Rettig; A. Hannemann (International Journal of Endocrinology)
Objective. Aldosterone and high-density lipoprotein cholesterol (HDL-C) are involved in many pathophysiological processes that contribute to the development of cardiovascular diseases. Previously, associations between the concentrations of aldosterone and certain components of the lipid metabolism in the peripheral circulation were suggested, but data from the general population is sparse. We therefore aimed to assess the associations between aldosterone and HDL-C, low-density lipoprotein cholesterol (LDL-C), total cholesterol, triglycerides, or non-HDL-C in the general adult population. Methods. Data from 793 men and 938 women aged 25–85 years who participated in the first follow-up of the Study of Health in Pomerania were obtained. The associations of aldosterone with serum lipid concentrations were assessed in multivariable linear regression models adjusted for sex, age, body mass index (BMI), estimated glomerular filtration rate (eGFR), and HbA1c. Results. The linear regression models showed statistically significant positive associations of aldosterone with LDL-C (β-coefficient = 0.022, standard error = 0.010, p=0.03) and non-HDL-C (β-coefficient = 0.023, standard error = 0.009, p=0.01) as well as an inverse association of aldosterone with HDL-C (β-coefficient = −0.022, standard error = 0.011, p=0.04). Conclusions. The present data show that plasma aldosterone is positively associated with LDL-C and non-HDL-C and inversely associated with HDL-C in the general population. Our data thus suggests that aldosterone concentrations within the physiological range may be related to alterations of lipid metabolism.